2021
DOI: 10.3389/fimmu.2021.754196
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Myeloid-Derived Suppressor Cells to Enhance the Antitumor Efficacy of Immune Checkpoint Blockade Therapy

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that are activated under pathological conditions, such as cancer, or mature myeloid cells that are converted immune-suppressive cells via tumor-derived exosomes, and potently support the tumor processes at different levels. Currently, multiple studies have demonstrated that MDSCs induce immune checkpoint blockade (ICB) therapy resistance through their contribution to the immunosuppressive network in the tumor micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 134 publications
0
20
0
Order By: Relevance
“…Reprogramming or reducing MDSCs can help reactivate the immune system's antitumor response. 113 Recently, an interesting nanoplatform was developed by Zhou et al to enhance pyroptosis-based immunotherapy and overcome immune escape mediated by MDSCs. 114 Pyroptosis, programmed cell death, can increase the immune response of tumor cells.…”
Section: Nanotechnological Targeting Strategies To Modulate Tme Of Pdacmentioning
confidence: 99%
“…Reprogramming or reducing MDSCs can help reactivate the immune system's antitumor response. 113 Recently, an interesting nanoplatform was developed by Zhou et al to enhance pyroptosis-based immunotherapy and overcome immune escape mediated by MDSCs. 114 Pyroptosis, programmed cell death, can increase the immune response of tumor cells.…”
Section: Nanotechnological Targeting Strategies To Modulate Tme Of Pdacmentioning
confidence: 99%
“…Tregs secrete immunosuppressive cytokines which inhibit cytotoxic T cell function or limit the number of IL-2 that can activate cytotoxic T cells. 124 Similar to Tregs, MDSCs 125,126 and TAMs 127,128 were found to negatively modulate the function of T cells in the TME by modulating tumour vasculature or pre-metastatic niche formation, producing various anti-inflammatory cytokines, and inducing epithelial-mesenchymal transition (EMT) of tumour cells. [125][126][127][128] For instance, Cervantes et al demonstrated that the co-culture of CAR-T cells with MDSCs could reduce the T cell production of IFNγ and inhibit the CAR-T cell activation.…”
Section: Immunosuppressive Cells and Cytokines Inhibit The Function O...mentioning
confidence: 99%
“…Studies indicate that regulatory T cells (Tregs) and other cell populations, namely, myeloid-derived suppressor cells (MDSCs; attracted to TME by low-grade chronic inflammatory signals) and tumor-associated macrophages (TAMs) ( 17 ), are mainly responsible for the immunosuppression observed in PC ( 18 ). Among them, MDSCs emerge as potential therapeutic targets ( 19 ).…”
Section: Prostate Cancer—epidemiologymentioning
confidence: 99%